the The Influence Of Feature Availability, Trust, And Convenience On The Satisfaction Of Mnc Motion Trade Users Among Students In Jabodetabek - Verry Cyasmoro (Cita konsultindo, 2024)
In this research study, quantitative techniques were used. The population of the study consists of active student users of the Motion Trade MNC Sekuritas application in the Greater Jakarta area (Jabodetabek). The sampling technique employed was purposive sampling with 200 respondents. Data analysis using SMART PLS indicated that the features variable positively affects user satisfaction with the Motion Trade application, the trust variable positively affects user satisfaction with the Motion Trade application, and the ease of use variable positively affects user satisfaction with Motion Trade MNC Sekuritas. Keyword: feature, trust, convenience, satisfaction